ANALISIS KEMAMPUAN PEMECAHAN MASALAH MAHASISWA DALAM MATA KULIAH MATEMATIKA DISKRIT PADA MATERI KOMBINATORIKA - Evi Triyani; Heni Pujiastuti (Universitas Ahmad Dahlan, 2021)
This study aims to determine the ability of problem solving in discrete mathematics courses on combinatorics material for the sixth semester students of Mathematics Education at Sultan Ageng Tirtayasa University. This type of research is a qualitative descriptive study. Where this study describes the results of the analysis of problem solving in students. The sample used in this study were 10 students. The instrument used was a test description of the ability to solve problems in combinatorics and interviews. The results in this study indicate that 1) The average level of problem solving abilities of students in combinatorics material is 69, which is included in the classification Good Enough; 2) There are factors that make it difficult for students to solve combinatorics problem solving, namely the factor of forgetting to work with what formulas and the confused factor to identify these combinatorics problems. Combinatorics problem solving skills can be easily resolved if you practice frequently. Keywords : Problem Solving, Combinatorics, Descriptive Qualitative Ability